Biogenic Synthesis, Characterization of Silver Nanoparticles from Candelula Officinalis Extract and Evaluation of their Antimicrobial Activity - Rashmi Arora; Anita Grewal (Nano Biomedicine and Engineering, 2015)
Synthesis of silver nanoparticles from root extract of Candelula officinalis (marigold) as a biomaterial is reported in the present study. Plant root extract has water soluble organic materials which help in the reduction of silver ions and stabilization of AgNPs. Aqueous solution of silver nitrate was treated with root extract of C. officinalis for the formation of AgNPs. The UV-Visible spectroscopy indicated an absorption peak at 423 nm, which indicates synthesis of AgNPs. Further characterization by Dynamic Light Scattering (DLS) showed size distribution profile of synthesized silver nanoparticles (AgNPs). Transmission electron microscopy (TEM) demonstrated the presence of spherical AgNPs in range of 14-40 nm. The formed silver nanoparticles showed good antimicrobial activity against various microorganisms viz. Eshcherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Candida albicans. AgNPs showed the maximum activity against Pseudomonas aeruginosa with a inhibition zone of 22 nm. Thus, the present study provides evidence of simple, rapid and environmental friendly route to synthesize AgNPs using aqueous root extract of Candelula officinalis.